2009
DOI: 10.1055/s-0028-1104610
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided Keyhole Evacuation of Spontaneous Supratentorial Intracerebral Hemorrhage

Abstract: The image-guided keyhole approach allowed prompt evacuation of SICH and resulted in a high rate of functional recovery and low mortality. This is a minimally invasive technique that is highly effective in immediate and complete hematoma evacuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…3,7 Barlas et al 3 reported an average reduction in hematoma volume of 97.5% (range 92.9%-100%), and they demonstrated significant improvements in both radiological and clinical data. Microsurgical evacuation has the advantage of immediate and near-complete hematoma removal, but it does require more cortical exposure and brain retraction than endoscopic techniques.…”
Section: Discussionmentioning
confidence: 98%
“…3,7 Barlas et al 3 reported an average reduction in hematoma volume of 97.5% (range 92.9%-100%), and they demonstrated significant improvements in both radiological and clinical data. Microsurgical evacuation has the advantage of immediate and near-complete hematoma removal, but it does require more cortical exposure and brain retraction than endoscopic techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Barlas et al demonstrated a 60% reduction in both mean midline shift and edema volume (p=0.005) with a minimally invasive technique for ICH removal. 65 Furthermore in a small study comparing medical management vs. medical management plus stereotactic endoscopic hematoma evacuation, Miller et al demonstrated a 30% absolute reduction in mortality in the surgically managed group. 66 …”
Section: Post-pci Intracranial Hemorrhagementioning
confidence: 99%
“…The functional outcomes in ICHs less frequently improve by surgery than those in subcortical or putaminal hemorrhages. [931] Several methods of minimally invasive surgery such as stereotactic-guided evacuation[8] and its modifications[41719] have been developed. Neuroendoscopic evacuation of ICHs has been the treatment modality of choice since the 1990s.…”
Section: Introductionmentioning
confidence: 99%